Stability of antibacterial modification of nanofibrous PA6/DTAB membrane during air filtration - Ryšánek, Petr; Čapková, Pavla; Štojdl, Jiří; Trögl, Josef; Benada, Oldřich; Kormunda, Martin; Kolská, Zdeňka; Munzarová, Marcela (Materials science & engineering. C, Materials for biological applications, 2019)
Stable antimicrobial nanofibrous membrane for air filtration based on polyamide 6 (hereafter PA6) modified by 1-dodecyltrimethylammonium bromide (DTAB) has been prepared by electrospinning using one-step technology, i.e. with modifying antimicrobial agent dissolved in spinning solution. Stability of antibacterial membrane function has been tested by air-blowing test to prove the permanency of chemical composition and antibacterial activity. X-ray diffraction, high-resolution scanning electron microscopy (HRSEM) revealed the effect of modifying agent on structure and morphology of PA6 nanofibres. X-ray photoelectron spectroscopy, electrokinetic analysis and antibacterial tests proved the stability of chemical composition and antibacterial activity after air-blowing tests. Special air-blowing device has been constructed for this purpose. The results prove the applicability so prepared membrane for a long-term air-conditioning.
Keywords: polymery; Caprolactam; Membranes, Artificial; Polymers; antiinfekční látky; kaprolaktam; vzduchové filtry; membrány umělé; Anti-Infective Agents; nanovlákna; Nanofibers; Air Filters